Clinical and Histological Comparison of Platelet-Rich Fibrin with Periodontal Dressing and Non-Eugenol Periodontal Dressing Alone on the Depigmented Gingival Epithelium - Km Sarika Gupta; Amit Wadhawan; Prashant Tyagi; Ankita Khare (Journal of Pharmacy and Bioallied Sciences)
Background: This study aims to assess and contrast the healing results, in terms of both histology and clinical appearance, after gingival depigmentation using diode laser application of the platelet-rich fibrin (PRF) membrane in contrast to non-eugenol periodontal dressing (Coe-Pak). Materials and Method: Thirty individuals in good health, aged between 18 and 50 years, were randomly divided into two groups, with each group consisting of 15 participants. One group underwent application of a PRF membrane along with periodontal dressing, while the other group received solely non-eugenol periodontal dressing. This procedure was performed in the intercanine region of the maxillary or mandibular arch for all participants. PRF was processed following the standardized procedure outlined by Choukroun. Patients underwent assessments for pain intensity using the visual analog scale (VAS) and for healing advancement using the Healing Index (HI) on the third and fifth days following treatment. Results: Statistically significant disparities were noted between the two study groups concerning the VAS, HI, epithelialization assessment, and histological observations. In the clinical assessment of epithelialization using toluidine blue, it was observed that areas treated with PRF+Coe-Pak showed significantly reduced staining, indicating enhanced wound healing compared to those treated with Coe-Pak alone. Conclusion: After depigmentation, the PRF+Coe-Pak group demonstrated enhanced patient comfort and facilitated an efficient wound-healing process.